Tax Assistant Mediation in The Behavioral Model of Tax Compliance in MSMEs - Ira Murwenie; Ramayani - Yusuf; Gunardi - Gunardi; Tatiek Ekawati Permana (University of Merdeka Malang, 2024)
This research examines how tax assistants, tax management, and the final PPh tax incentives (PP 23/2018) might increase Bandung Regency SMEs' tax knowledge and compliance. The quantitative descriptive research technique used simple random selection for MSMEs with active NPWP status at the DJP KPP office in Bandung Regency. This research uses PLS SEM and SEMPLS3 software to analyze 132 MSMEs in agricultural, culinary, and fashion. Tax management mediated by a tax assistant has a 17.7% favorable impact on tax compliance. Tax Assistant improves tax compliance by 0.626, or 62.6%. Tax Management (TMP) improves the Tax Assistant (TEA) by 55.0%. This research concludes that the low level of SME tax compliance in Bandung Regency is more due to a lack of knowledge in techniques for calculating, paying, and reporting MSMEs final income tax (PPh), where a tax assistant becomes very important in aiding management in MSMEs tax compliance, and that the findings are consistent with the Expected Utility Tax Compliance Theory